Engineered zinc oxide-based nanotherapeutics boost systemic antibacterial efficacy against phloem-restricted diseases. Issue 8 (7th July 2022) - Soliman, Mikhael; Lee, Briana; Ozcan, Ali; Rawal, Takat B.; Young, Mikaeel; Mendis, Hajeewaka C.; Rajasekaran, Parthiban; Washington, Torus; Pingali, Sai Venkatesh; O'Neill, Hugh; Gesquiere, Andre; De La Fuente, Leonardo; et al.
Abstract : Defect engineering at the surface of zinc oxide sub-5 nm nanoparticles provides a systemic nanotherapeutic with significant field efficacy against citrus HLB disease. Abstract : Delivering active ingredients with high antibacterial efficacy at infected sites in plants is essential to reach global goals for food security and sustainable agriculture productivity. Engineering nanomaterials is a suggested approach to attain systemic delivery of antibacterial active ingredients, thereby improving the treatment efficacy and minimizing harmful effects related to leaching in the environment. Herein, surface defect engineering of nanotherapeutics is used as a new form of active ingredient for systemic antimicrobial action in the phloem. The nanoparticle-based formulation, called Zinkicide®, features a spherical particle composed of a zinc oxide (ZnO) core and zinc peroxide (ZnO2 ) shell with a total diameter below 5 nm. This formulation exhibits significant efficacy to manage citrus huanglongbing (HLB) disease as seen by the decrease in severity of symptoms and the increase from ∼7% to 19% of medium and large fruits in HLB infected citrus groves, during field trials. Further analysis of the bacterial responses to Zinkicide® in situ indicates high potency at a concentration as low as 9–18 μg mL −1 and biofilm growth inhibition at a concentration of 50 μg mL −1 . Nanoscale infrared spectroscopy reveals morphology and secondary structure changes of the bacterial membrane upon treatment. The origin of the changes is considered, based on the optical signatures of the nanoparticles, indicative of surface defects. These inform a theoretical description of the participation of a ZnO2 /ZnO surface containing a pair of missing O atoms in the production of reactive oxygen species (ROS). The key participation of defects in the antibacterial action is confirmed experimentally by the slow decrease in antibacterial efficacy as nanoparticles age in media with passivation effects on the surface. This study reveals the importance of size of the nanoparticle and nature of surface defects in the design of nanotherapeutics for targeted delivery and antibacterial activity.